Accounting Treatment of Inherent versus Incentive Uncertainties and the Capital Structure of the Firm - LIANG, PIERRE JINGHONG; ZHANG, XIAO-JUN (Journal of Accounting Research, 2006)
This paper studies the accounting treatment of uncertainty and how it affects a firm's capital structure. We distinguish two sources of uncertainty that raise reliability concerns: inherent uncertainty and incentive uncertainty. By inherent uncertainty, we refer to uncertainty about the quality of raw information regarding future cash flows. By incentive uncertainty, we refer to uncertainty about the quality of accounting numbers conveying the raw information. We explore features of accounting that can effectively deal with these two types of uncertainties in order to aid in the debt-equity decision of the firm. To handle inherent uncertainty, preferable accounting involves flexible revenue/expense recognition rules that recognize more profit when the uncertainty level is low. To deal with incentive uncertainty, a stringent revenue/expense recognition rule may be desirable to fend off management's opportunistic reporting behavior. Inflexible accounting rules cause a firm's financing choices to deviate from what would hold with complete information. Given any accounting rule, an information environment with a lower (higher) uncertainty regarding future cash inflows leads to higher (lower) expected debt financing. This is because assessed default risk is increasing in the uncertainty of future cash inflows, holding the uncertainty of the outflows constant.